Advanced Maternal Age Impairs Myelination in Offspring Rats - Han, Wei; Pan, Ya'nan; Han, Ziyao; Cheng, Li; Jiang, Li (Frontiers in Pediatrics, 2022)
The effects of advanced maternal age (AMA) on the neurodevelopment of offspring are becoming increasingly important. Myelination is an important aspect of brain development; however, a limited number of studies have focused on the effects of AMA on myelination in offspring. The current study aims to evaluate the association between AMA and myelin sheath development in offspring. We studied the learning and memory function of immature offspring using the novel object recognition test. Then, we investigated the expression of myelin basic protein (MBP) in the immature offspring of young (3-month-old) and old (12-month-old) female rats at different time points (14, 28, and 60 days) after birth with immunofluorescence and western blotting. The myelin sheath ultrastructure was observed with transmission electron microscopy in immature and mature offspring. Extracellular signal-regulated kinase 1 and 2 (ERK1/2) and phosphorylated ERK1/2 (p-ERK1/2) were investigated by western blot in immature offspring at the above time points. AMA impaired the memory function of offspring during early postnatal days. The MBP expression level gradually increased with postnatal development in the offspring of both the AMA and Control (Ctl) groups, but the MBP level in the offspring of the AMA group was lower than that of the Ctl group at 14 days after birth. In addition, the ultrastructure of the myelin sheath was defective in AMA offspring during the early postnatal period; however, the myelin sheath was not significantly affected in offspring during adulthood. Interestingly, ERK phosphorylation at 14 days after birth was lower in AMA offspring than in Ctl offspring. However, ERK phosphorylation at 28 days after birth was higher in AMA offspring than in Ctl offspring. The peak of ERK phosphorylation in the AMA group was abnormal and delayed. Our results indicated that AMA is associated with poor developmental myelin formation in offspring. The ERK signaling pathway may play an essential role in the adverse effects of AMA on the offspring myelin sheath development.